2008
DOI: 10.1110/ps.036012.108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human receptor activity‐modifying protein 1 extracellular domain

Abstract: Receptor activity-modifying protein (RAMP) 1 forms a heterodimer with calcitonin receptor-like receptor (CRLR) and regulates its transport to the cell surface. The CRLRÁRAMP1 heterodimer functions as a specific receptor for calcitonin gene-related peptide (CGRP). Here, we report the crystal structure of the human RAMP1 extracellular domain. The RAMP1 structure is a three-helix bundle that is stabilized by three disulfide bonds. The RAMP1 residues important for cell-surface expression of the CRLRÁRAMP1 heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 37 publications
5
65
0
Order By: Relevance
“…It belongs to a family of three receptor activity-modifying proteins (RAMP1, -2, and -3) that affect the glycosylation, membrane trafficking and ligand recognition properties of the calcitonin receptor-like receptor, a family B receptor distantly related to the glucagon receptor (33). However, similar to the homologous RAMP1 expressed in Escherichia coli (34), the four extracellular cysteines of RAMP2 are probably involved in two conserved disulfide bridges and therefore not available to cysteine reagents. RAMP2 is therefore unlikely to be responsible for the effect of MTSET on glucagon recognition in HEK cells.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to a family of three receptor activity-modifying proteins (RAMP1, -2, and -3) that affect the glycosylation, membrane trafficking and ligand recognition properties of the calcitonin receptor-like receptor, a family B receptor distantly related to the glucagon receptor (33). However, similar to the homologous RAMP1 expressed in Escherichia coli (34), the four extracellular cysteines of RAMP2 are probably involved in two conserved disulfide bridges and therefore not available to cysteine reagents. RAMP2 is therefore unlikely to be responsible for the effect of MTSET on glucagon recognition in HEK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies elucidated the folds of the CLR and RAMP1 and -2 ECDs and revealed how they interact in the absence of peptide ligands. [15][16][17] The CLR ECD fold is common to class B GPCR ECDs and consists of an N-terminal a-helix followed by a short consensus repeat fold that is composed of two b-sheets each with two b-strands. Three conserved disulfide bonds hold the secondary structure elements together.…”
mentioning
confidence: 99%
“…Smallmolecule antagonists discussed below act by blocking the binding to the peptide-binding cleft [61]. RAMP1 is involved in processing and presenting the CGRP receptor to the cell surface and helps determine the relative affinity and sensitivity of the receptor [62,63]. Zhang et al [64] showed that RAMP1 is functionally rate limiting for CGRP receptor activity in the trigeminal ganglion, suggesting that elevated RAMP1 could sensitize migraine sufferers to CGRP actions [64].…”
Section: The Receptormentioning
confidence: 99%